PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PENGECORAN LOGAM PT. SINAR SEMESTA (Studi Kasus Tentang Perilaku Penggunaan Alat Pelindung Diri (APD) Ditinjau Dari Pengetahuan Terhadap Potensi Bahaya Dan Resiko Kecelakaan Kerja Pada Pekerja Pengecoran L - Novianto, Nanang Dwi (Jurnal Kesehatan Masyarakat (Undip), 2015)
Foundry industry is an industry that processes metal ore into finished objects. The iron casting in foundry in Ceper Klaten is using the temperate reaches to 1600° C. In this industry, most of workers do not use the Personal Protective Equipment (PPE) in the workplace, although there are many dangers that can be found such as the high temperature, the infrared radiation, the heat of metal splash, the dust of combustion, the electrical induction, and the flake of metals.The purpose of this study is to analyze the behavior of foundry workers toward the use of (PPE) that is evaluated from the awareness of the potency of dangers and the risks of accidents in PT. Sinar Semesta, Batur, Ceper, Klaten. This research is a qualitative descriptive study that involves six informants, which consists of four main informants and two triangulation informants. The data collection is done through the direct observation and in-depth interviews using questionnaires. The results of this study indicate that the foundry workers in PT. Sinar Semesta Desa Batur, Ceper, Klaten has a low level of awareness about the use of Personal Protective Equipment (PPE) and the risks of the dangers that might threaten their safety in the workplace. These results were obtained from in-depth interviews conducted by the researcher in the field that indicates if the metal foundry workers in PT. Sinar Semesta has an indifferent attitude towards the use of Personal Protective Equipment (PPE), as expressed by almost all respondents stated that they felt uncomfortable, hot and sultry wear safety equipment such as PPE.It is recommended to prepare the company regulations, requiring the use of PPE and provide opportunities for workers to follow safety and healthy training, as well as creating a comfortable working environment.